MOLECULAR CHARACTERIZATION AND PHYLOGENETIC ANALYSIS OF MYCOPLASMA SYNOVIAE ISOLATED FROM CHICKEN - A. Rasool; A. A. Anjum; M. Rabbani; M. Lateef; F. Akhter; H. Afroz; J. Muhammad; M. Nawaz (Journal of Animal and Plant Sciences, 2018)
Mycoplasma synoviae is one of the paramount causes of economic losses for poultry industry. Present study was carried out with the aim to isolate, identify and characterize M. synoviae from suspected chicken. Tracheal and cloacal swabs samples (n=500), collected from suspected chicken, were cultured on Modified Frey, s medium for isolation of Mycoplasma. Preliminary identification of Mycoplasma was done by culturing and biochemical characterization. Partial 16 S r RNA was amplified and sequenced for confirmation and molecular identification of M. synoviae. For strain identification and phylogenetic analysis, partial amplification and sequence of vlhA gene was performed. Out of 500 samples, Mycoplasma was successfully isolated from 40 samples. Out of 40 mycoplasma isolates, 20 were identified as M. synoviae by specie specific 16S ribosomal RNA gene, partial amplification (~213 bp). The vlhA gene was also successfully partially amplified (~375 bp) and sequenced from five isolates. GenBank accession numbers of reported local isolates in this study are KJ130523-KJ130542.and KP316017-KP316021 respectively.
Keywords: Mycoplasma; fried egg colonies; 16S rRNA; vlhA gene